Long-term effectiveness of the nine-valent human papillomavirus vaccine: Interim results after 12 years of follow-up in Scandinavian women - Susanne K. Kjaer; Thea E. Hetland Falkenthal; Karin Sundström; Christian Munk; Tina Sture; Oliver Bautista; Sonali Rawat; Alain Luxembourg (Taylor & Francis Group, 2024)
A pivotal study in women aged 16-26 years demonstrated that the nine-valent human papillomavirus (9vHPV) vaccine was efficacious against high-grade cervical dysplasia related to the HPV types covered by the vaccine. To evaluate whether effectiveness remains above 90% for up to 14 years post-vaccination, a long-term follow-up (LTFU) extension of the study was conducted in Denmark, Norway, and Sweden (N = 2,029). Interim findings at 12 years post-vaccination are reported. Effectiveness of the vaccine was measured by comparing the percentage reduction in incidence of HPV16/18/31/33/45/52/58-related high-grade cervical dysplasia in the LTFU cohort with the expected incidence in an unvaccinated cohort. Cervical pre-cancer/cancer diagnoses were identified using national health registries. Tissue samples were obtained from national and regional biobanks for polymerase chain reaction HPV testing, and pathology diagnosis adjudication. Potential waning of vaccine effectiveness and statistical significance were assessed using a control chart method. During LTFU, there were no cases of HPV16/18/31/33/45/52/58-related high-grade cervical dysplasia over 10,396.2 person-years' follow-up in the per-protocol effectiveness population (n = 1,628). No signals indicated vaccine effectiveness decreasing below 90%. Statistically significant protection was provided by the 9vHPV vaccine through at least 10 years, with complete, although not statistically significant, effectiveness through 12 years.